Monosony in labor markets: Theory, evidence, and public policy - Alderman, Brianna L.; Blair, Roger D. (New York Cambridge University Press, 2024)
The economics of monopsony power results in lower wages and other forms of compensation, as well as reduced employment. Wealth is transferred from workers to their employers. In addition, the employer's output is reduced, which leads to increased prices for consumers. Monopsony in Labor Markets demonstrates that elements of monopsony are pervasive and explores the available antitrust policy options.